Out-of-pocket payments and associated factors among hypertensive patients insured under the National Health Insurance Scheme in a referral hospital, Ghana - Angela Nana Esi Ackon; Hubert Amu; Martin Amogre Ayanore (PLoS ONE, 2026)
Introduction Out-of-pocket (OOP) payments are a common component of healthcare financing in many low-and middle-income countries including Ghana. Despite implementation of the National Health Insurance Scheme in Ghana which is expected to protect against catastrophic OOP payments, patients still make some form of payments with its attendant negative implications for improved health status. We examined the prevalence and self-reported effects of OOP payments among hypertensive patients insured under the National Health Insurance Scheme attending a referral hospital in Hohoe, Ghana. Methods This was a cross-sectional study conducted among 389 hypertensive patients between February and May 2022 using a structured questionnaire. Data collected were analysed using Stata software version 15. We employed descriptive statistics and logistic regression in analysing the data. Statistical significance was considered at p < 0.05. Results A total of 97.2% respondents made OOP payments in receiving healthcare with 97.1% of those who made such payments having made them at the point of receiving drugs. Difficulty in making OOP payments was reported by 29.1% of the respondents and this was associated with ever borrowing money to cover health expense (aOR=2.52; 95% CI: 1.31–4.88; p = 0.006), OOP payments affecting hospital attendance (aOR=5.52; 95% CI: 2.74–11.11; p < 0.001) and having an alternative form of treating hypertension (aOR=2.93; 95% CI: 1.60–5.38; p = 0.001). Conclusion OOP payments are widespread in the utilisation of healthcare for hypertensive patients. This raises concerns about progress towards the attainment of Sustainable Development Goals (SDGs) 3.4 which seeks to control non-communicable diseases and SDG 3.8 which seeks to ensure universal health coverage. Medications or drugs are the major healthcare services for which individual hypertensive patients made OOP payments thus highlighting the need ensure availability and accessibility of drugs to meet the global targets of SDG 3 and due to the long-term treatment requirements of hypertension.